Effect of copper addition on the properties of TiO2 coatings deposited by air plasma spray process - Abd Rahim, Toibah; Amir, Nur Izzah Atira; Mohamad, Noraiham; Adibah Haneem, Mohamad Dom; Omar, Nooririnah; Yusuf, Yusliza; Abu Bakar, Ilyani Akmar; Mohamad Juoi, Jariah (Semarak Ilmu Publishing, 2023)
Mild steel is a crucial engineering material with numerous engineering uses. Still, wear frequently causes mechanical parts made of mild steel to fail. Coatings prepared using an air plasma spray process may be a good choice for improving the surface properties of mild steel. Composite materials, such as Cu-TiO2, can potentially improve the properties of mild steel, such as hardness, wear, and corrosion resistance. This study aims to investigate the effect of copper (Cu) addition on the microstructure, surface roughness, and wear properties (coefficient of friction (COF)) of the titanium dioxide (TiO2) coating prepared by the air plasma spray (APS) method. The TiO2 powder and 30 wt% Cu powder in the micron-sized range were mixed by the ball milling prior to the coating process. The particle size distribution and microstructure of the TiO2 and Cu feedstock powders were studied using particle size analyzer (PSA) and field emission scanning electron microscopy (FESEM). Then, the properties of the as-prepared TiO2and Cu-TiO2 coatings were characterized using FESEM, X-ray diffractometer (XRD), 3D non-contact profilometer and pin-on-disc tester. The TiO2 and Cu-TiO2 coatings were composed of well-melted and partially melted particles. The presence of Cu in the TiO2 coating led to the deposition of a thicker coating of about 242 μm, which is 28.7% thicker compared to the TiO2 coating alone. Compared to pure TiO2 coating, Cu-TiO2coating showed lower surface roughness with less pores and microcracks, resulting in a reduced coefficient of friction. The finding of this study suggested that Cu addition to the TiO2 coating on the mild steel substrate may produce better protective coating for wear and corrosion application.